Sexual behaviour and condom use among individuals with a history of symptomatic genital herpes. Issue 1 (3rd February 2006) - Rana, R K; Pimenta, J M; Rosenberg, D M; Warren, T; Sekhin, S; Cook, S F; Robinson, N J
Abstract : Objectives: This study describes the differences in sexual behaviour in individuals with genital herpes (GH) during "symptomatic" and "asymptomatic" periods of the disease. Methods: A cross sectional questionnaire was undertaken by 1193 individuals attending clinics between 1998 and 2001. All participants in this analysis were in heterosexual, monogamous partnerships, self identified with a history of symptomatic GH and with confirmed HSV-2 infection. Results: Sexual activity reported during asymptomatic v symptomatic periods of GH was 98% v 40% (p<0.001), 76% v 29% (p<0.001), and 25% v 11% (p<0.001) for vaginal, oral, and anal intercourse, respectively, while "always" condom use during asymptomatic and symptomatic periods was 20% v 35% (p<0.001), 2% v 7% (p<0.001), and 10% v 15% (p = 0.131), respectively. The proportion of individuals who either abstained from vaginal intercourse or "always" used condoms was 21% v 74% (p<0.001), for asymptomatic v symptomatic periods. Multivariable analyses indicated that factors associated with engaging in intercourse during symptomatic periods of GH included current intrauterine device use (adjusted odds ratio (aOR) = 2.96, 95% confidence interval (CI) = 1.46 to 6.02); living in Latin America (aOR = 2.16, CI = 1.19 to 3.91) or Europe (aOR = 1.67, CI = 1.21 to 2.28), compared with North America; previous sexually transmitted disease (aOR = 1.42, CI = 1.08 to 1.89); a higher number of sexual acts per month (aOR = 1.09, CI = 1.06 to 1.11); and a higher number of GH recurrences per year (aOR = 1.08, CI = 1.03 to 1.12). Conclusions: These data indicate that the majority of people with GH either abstained from intercourse or "always" used condoms during symptomatic periods of GH. However, condom use was relatively low during asymptomatic periods in comparison with symptomatic periods. These results highlight that further education on GH prevention is warranted, particularly for symptomatic periods.